Improving the Students’ Writing Skill by Using Clustering Technique At Tenth Grade of MA Al- Kautsar - Mardin Silalahi; Lestari Simarmata (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2022)
The objective of the research is find out the effect of Using Clustering technique on students’ Writing Skill at Tenth Grade of MA Al-Kautsar. This research used quantitative approach with experimental method. The samples in this study was the tenth grade students of MA Al-Kautsar. The researcher used simple random sampling by making lottery to take the sample. The tenth grade of MA Al-Kautsar was divided into two groups, namely 30 students as group 1 and 30 students as group 2. Group 1 as control group and group 2 as experiment group. The instrument used in the study was a written test in the pre-test and post-test. The data was analyzed by using SPSS. The findings indicate that the students’ score pre-test in control group are 1593 where the mean is 53,10 and the students’ score post test in control group are 1809 where the mean is 60,30. Before the treatment of clustering technique , the students’ prior knowledge in writing descriptive text was less since the pre- test data are 1605 where the mean is 53,50. After the treatment of using clustering technique, the students’ ability in writing descriptive text had been improved since the post-test are 2211 where the mean is 73,70. Based on testing hypothesis of post-test scores, it is found tcount ( 7,91) > ttable (1,69) at the significance level ɑ= 0,05 and degrees of freedom (df)= 29. Ho is rejected and Ha is accepted, it means that there was difference in students learning outcomes by using clustering technique and without using clustering technique. So, From the result, the researcher concluded that using clustering technique effect significantly to improve students’ writing skill at tenth grade of MA Al- Kautsar